PENANGANAN PERMUKIMAN KUMUH DENGAN PENINGKATAN KUALITAS SARANA DAN PRASARANA DI PANCURAN KOTA SALATIGA - Wahyu Nugroho .; Puji Astuti .; Neny Marlina . (Journal of Politic and Government Studies, 2017)
HANDLING OF SLUMS BY IMPROVING THE QUALITY OF FACILITY AND INFRASTRUCTURE IN PANCURAN SALATIGA CITYWAHYU NUGROHO(POLITICAL AND GOVERNMENT DEPARTMENT OF SOCIAL AND POLITICAL SCIENCE FACULTY, DIPONEGORO UNIVERSITY, SEMARANG)ABSTRACTPancuran is an Settlement area in Salatiga city which includes in dirty settlement criteria. The citizen compactness makes high habitation necessary but it is not balanced with enough land availability, in the end there are so many empty spaces which is built. Incorrect land utilization which is followed by improper supporting housing infrastructure leads to problem which is more difficult to be handled.The type of this research is descriptive analysis through qualitative approach which was meant to present description about situation or phenomenon in research specifically. Data resources were from primary data and secondary data. Informant determining was done by purposive sampling technique at Dirty Settlement in Pancuran. Data collecting, researcher used 3 (three) methods were interview method, observation and documents study.Result of this research shows that government has had some programs to solve dirty settlement problem in Pancuran. Tose programs are house renovation, build IPAL Piping Communal, build Rwhall and infrastructure renovation. Obstacles which is faced by the overnment are land unavailability, low income, society behaviour, land ownership and land status, and lack of traction on law enforcement.In implementing proram, socialization which was done had run well and got an active response from society but unfortunately, nowadays those activities has stopped. Meanwhile, lack of coordination with society had happened because they were seemed blaming each other.Suggestions for the government are they should not only mantain settlement physically but they have to be able to give awareness to society about rules loyality and the importance to keep environment.Kata Kunci: Slums, Problem Solving, Effectivness